2010
DOI: 10.1111/j.1365-2966.2010.16221.x
|View full text |Cite
|
Sign up to set email alerts
|

Polarization towards the young open cluster NGC 6823

Abstract: We present multiwavelength linear polarimetric observations of 104 stars towards the region of young open cluster NGC 6823. The polarization towards NGC 6823 is dominated by foreground dust grains and we found evidence for the presence of several layers of dust towards the line of sight. The first layer of dust is approximately located within 200 pc towards the cluster, which is much closer to the Sun than the cluster itself (∼2.1 kpc). The radial distribution of the position angles for the member stars is fou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 40 publications
4
18
0
Order By: Relevance
“…The instrumental polarization of AIMPOL on the 1.04-m ST has been monitored since 2004 for different projects and is 0.1% in different bands (e.g., Rautela et al 2004;Medhi et al 2007Medhi et al , 2008Medhi et al , 2010Eswaraiah et al 2011Eswaraiah et al , 2012. No correction for the instrumental polarization was applied to the data obtained with IFOSC since the instrumental polarization of the instrument on the 2-m telescope is <0.05 per cent.…”
Section: Polarimetrymentioning
confidence: 99%
“…The instrumental polarization of AIMPOL on the 1.04-m ST has been monitored since 2004 for different projects and is 0.1% in different bands (e.g., Rautela et al 2004;Medhi et al 2007Medhi et al , 2008Medhi et al , 2010Eswaraiah et al 2011Eswaraiah et al , 2012. No correction for the instrumental polarization was applied to the data obtained with IFOSC since the instrumental polarization of the instrument on the 2-m telescope is <0.05 per cent.…”
Section: Polarimetrymentioning
confidence: 99%
“…In the majority of polarimetric studies of open clusters, it was found that the alignments of polarization vectors are almost parallel to the direction of the Galactic plane (e.g. Martínez et al 2004;Vergne et al 2007;Medhi et al 2007;Orsatti et al 2010;Medhi et al 2010;Eswaraiah et al 2011), while toward some other lines of sight, the second component of the magnetic field was also found, which was slightly inclined to the Galactic plane (Medhi et al 2008;Eswaraiah et al 2012). Davis & Greenstein (1951) suggested the dominant mechanism for alignment of dust grains in the ISM could be due to the presence of the small non-conservative torque produced by paramagnetic relaxation, and that this torque tends to align the short axis of the rapidly spinning grain along the magnetic field.…”
Section: Results Analysis and Discussionmentioning
confidence: 99%
“…The gain and the read-out noise of the CCD are 11.98 e − /ADU and 7.0 e − , respectively. Four sets of exposures of each 60 s were made on both the nights of observation.The detailed description of the instrument is given in Rautela et al (2004) and Medhi et al (2008Medhi et al ( , 2010.…”
Section: Observation and Data Reductionmentioning
confidence: 99%